2008
DOI: 10.1111/j.1444-2906.2008.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of live food organisms and commercial dry feeds used for seed production of amberjackSeriola dumerili

Abstract: To improve the nutritional quality of live foods and dry feeds ordinarily used for the seed production of amberjack Seriola dumerili, the nutrient contents of rotifers, Artemia nauplii and commercial feeds used in two larval production stations were evaluated. For comparison of the nutrient contents, artificially produced larvae, wild-caught juveniles and wild zooplankton samples were also analyzed. The proportions of 22:6n-3 in the polar lipid of the cultured larvae increased by feeding the dry feeds. The tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…Previous results from Yamamoto et al . ; suggest that in Artemia ‐feeding stages at least 1.4–2.6% of DHA and 2.3–4.1% of n‐3 HUFAs are needed in the diet of the yellowtail S. quinqueradiata . Present results showed that S. rivoliana eggs contents 16.5% total fatty acids (TFA) (about 4.3% DW) in DHA and n‐3 HUFA were as high as 26.9% TFA (7.1% DW) suggesting even higher EFA requirements for this species, than for S. quinqueradiata .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous results from Yamamoto et al . ; suggest that in Artemia ‐feeding stages at least 1.4–2.6% of DHA and 2.3–4.1% of n‐3 HUFAs are needed in the diet of the yellowtail S. quinqueradiata . Present results showed that S. rivoliana eggs contents 16.5% total fatty acids (TFA) (about 4.3% DW) in DHA and n‐3 HUFA were as high as 26.9% TFA (7.1% DW) suggesting even higher EFA requirements for this species, than for S. quinqueradiata .…”
Section: Discussionmentioning
confidence: 96%
“…The relation between larval welfare and essential fatty acids, such as 20:5n-3 (EPA), 22:6n-3 (DHA) and 20:4n-6 (ARA), has been emphasized in early stages of development for different marines species (Izquierdo 1996), with 'shock syndrome' being one of the indication of EFA limitations in the diets (Izquierdo et al 1989). Previous results from Yamamoto et al 2008; suggest that in Artemiafeeding stages at least 1.4-2.6% of DHA and 2.3-4.1% of n-3 HUFAs are needed in the diet of the yellowtail S. quinqueradiata. Present results showed that S. rivoliana eggs contents 16.5% total fatty acids (TFA) (about 4.3% DW) in DHA and n-3 HUFA were as high as 26.9% TFA (7.1% DW) suggesting even higher EFA requirements for this species, than for S. quinqueradiata.…”
Section: Survival and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…and Artemia have been shown to have dramatically lower concentrations of taurine than calanoid copepods, a common larval prey item in the wild (Yamamoto et al . ). Yamamoto et al .…”
Section: Introductionmentioning
confidence: 97%
“…Fewer studies have focused on fish larvae (Chen, Takeuchi, Takahashi, Tomoda, Koisi & Kuwada ; Salze, McLean & Craig ; Matsunari, Hashimoto, Iwasaki, Oda, Masuda, Imaizumi, Teruya, Furuita, Yamamoto, Hamada & Mushiake ). Marine fish larvae typically consume planktonic prey items in the wild, such as copepods, that have been shown to contain high levels of taurine, suggesting that the physiological requirement for taurine may be high during this stage of development (Conceição, van der Meeren, Verreth, Evjen, Houlihan & Fyhn ; Helland, Nejstgaard, Humlen, Fyhn & Bamstedt ; van der Meeren, Olsen, Hamre & Fyhn ; Yamamoto, Teruya, Hara, Hokazono, Hashimoto, Suzuki, Iwashita, Matsunari, Furuita & Mushiake ; Maehre, Hamre & Elevoll ). Conversely, two typical live prey items used for culturing marine fish, rotifers ( Brachionus sp.)…”
Section: Introductionmentioning
confidence: 99%